Penal labour in the constitutional context: a comparison of South African and Germany. - Achelis, Felicitas (School For Advanced Legal Studies, 2023)
One of the most important reasons for doing comparative work in the field of law, is to get a better understanding of the legal jurisdictions of other countries. Studying the law of another country also enables one to understand one's legal jurisdiction in a better way. It helps one to see well-established principles in a new light and to ask questions about the continued applicability of such principles